“EVALUATION OF RADIATION DOSE OF CT ABDOMEN AND THORAX” (CAHIERS MAGELLANES-NS, 2024)
Computed tomography is higher modality of X-ray imaging. In computed tomography the doses are generally expressed in CTDIVol, DLP. CTDIvol and DLP doses were obtained from routine Abdomen and chest CT examination. The study was carried out in 160 patients (100 abdomen & 60 thorax). The data were recorded & analysed with Origin software . The paired sample t test was used to compare CTDIvol (mGy) and DLP (mGy*cm) of both the abdomen and thorax. The mean of CTDIvol was 18.71 with S.D. 4.75, mean of CTDIvol was 35.21 with S.D. 16.81 and the mean of DLP was 806.0 with S.D. 112.7, mean of DLP was 713.9 with S.D. 134.4 respectively. There was significant difference (p > 0.05) in CTDIvol and DLP respectively. t-test was performed to compare CTDIvol and DLP of Abdomen & Thorax according to gender. the mean of CTDIvol in male was 16.2 ,in female mean was 16.9 and the DLP mean in male was 842.9 and in females 819.7, the mean of CTDIvol in male was 16.3 in females mean was 16.5 and the mean of DLP in males was 696.2 and in females mean was 759.7 respectively. There were no difference in CT radiation doses in the abdomen and thorax groups according gender. The Pearson correlation coefficient (“r”) was used to find the relation of BMI with CTDIvol and DLP in Abdomen & Thorax .There was a negative correlation of BMI with CTDIvol and positive correlation with DLP.There was a positive correlation of BMI with CTDIvol and negative coorrelation with DLP respectively.